Reconfigurable Vacuum Sample Holder for Through-Silicon Microscopy and Laser-Assisted Bonding - Aleksandr Andreevich Vlasov; Topi Uusitalo; Heikki Virtanen; Jukka Viheriala; Mircea Guina (IEEE Photonics Journal, 2023)
Current development trends concerning miniaturizing of electronics and photonics systems are aiming at assembly and 3D co-integration of a broad range of technologies including MEMS, microfluidics, wafer level optics, multilayered structures with through-silicon vias connection, and silicon photonics. Modern integration processes impose severe requirements on the design and functionality of research and assembly setups and their parts. In this work we demonstrate a simple, reliable, and cost-effective reconfigurable vacuum sample holder that ensures fast reconfiguration for electronic and photonic integration using laser assisted bonding (LAB) processes. The design is compatible with IR through-silicon microscopy with top and bottom irradiation/illumination architectures, which makes this concept instrumental for a large variety of research, assembly, lithography, and wafer bonding setups.